Extracorporeal life support for acute respiratory distress syndromes - Don Hayes; Joseph D Tobias; Jasleen Kukreja; Thomas J Preston; Andrew R Yates; Stephen Kirkby; Bryan A Whitson (Annals of Thoracic Medicine, 2013)
The morbidity and mortality of acute respiratory distress syndrome remain to be high. Over the last 50 years, the clinical management of these patients has undergone vast changes. Significant improvement in the care of these patients involves the development of mechanical ventilation strategies, but the benefits of these strategies remain controversial. With a growing trend of extracorporeal support for critically ill patients, we provide a historical review of extracorporeal membrane oxygenation (ECMO) including its failures and successes as well as discussing extracorporeal devices now available or nearly accessible while examining current clinical indications and trends of ECMO in respiratory failure.